Hyperthyroidism, Hyperfunctioning Thyroid Nodule, and Thyroid Cancer in a Young Female: a Rare and Unusual Coexistence - Hernán-Martínez, José; Uzcategui, María; Corder, Eric; Castillo, Manuel; Sostre, Samuel; Alicea, Luz (Puerto Rico Health Sciences Journal, 2010)
The prevalence of concomitant thyroid carcinoma with Grave’s disease has been reported to range from 0 to 10%. Many controversies exist in the literature regarding the diagnostic workup and management in these types of patients. We are reporting a case of a 31 year old woman who had Graves’ disease, a palpable thyroid nodule, and results from a thyroid scan revealed a “hot” nodule. Interestingly, an ultrasound guided FNA of the “hot” nodule showed papillary thyroid microcarcinoma. Finally, a total thyroidectomy showed multilobar tumor involvement. The diagnostic tools employed to establish the proper management strategy for this patient were based on data in the literature that is full of discrepancies. The fact that Grave’s disease occurs concomitantly with thyroid cancer, specifically the papillary type, is an indisputably rare combination. One rare feature on our clinical case was the reported malignancy of a papillary carcinoma within a “hot” nodule which usually is much less that 1%. Many studies describe an increasing incidence of Grave’s disease patients with concomitant papillary thyroid carcinoma. One possible explanation for these findings could be improvements in medical technology of screening tools. We propose that, thyroid ultrasonography should be integrated in the diagnostic workup in patients presenting with Graves’ disease, especially in those presenting with palpable nodules. Fine needle biopsy should not be restricted to cold nodules. [P R Health Sci J 2010;1:78-82]